Formação de formadores e intercompreensão - Andrade, Ana Isabel; Martins, Filomena; Pinho, Ana Sofia (Educazione Linguistica Language Education, 2019)
Teacher education is a complex field, as it mobilises different knowledge domains, intervention contexts and multiple actors. The intervention in this field and the identification of the most adequate pathways to adopt, is perceived as difficult. With the purpose of providing support to tackle with such challenge, a teacher education framework for didactics of intercomprehension (REFDIC) was designed. In this chapter, we search to identify its research potential, based on the analysis of texts on the topic of intercomprehension in education processes written by school teachers in the context of pre- and in-service courses, which took place in Higher Education institutions in Portugal.